KONSEP CRITICAL PEDAGOGY HENRY A. GIROUX - Utami, Ichwani Siti; Alfian, Adam (Prodi PPKn FKIP Universitas Pamulang, 2017)
This article to discuss the critical pedagogy Henry A. Giroux, trough a philosophical-historical approach with the type of literature study. Giroux is one of the thinkers as well as developing critical pedagogy, the author tries to describe the concept of critical pedagogy Henry A. Giroux in some of his works. Critical pedagogy is not the new discourse in the scientific field of education in Indonesian, but the authors consider it necessary to reintroduce the concept of critical pedagogy, especially for those who focus on critical theory studies that have been developed by Frankfurt School. And describes the discourse of implementation of critical pedagogy for the advancement of Indonesian education.